IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENGIDENTIFIKASI KEMAMPUAN BERPIKIR KREATIF MAHASISWA MATEMATIKA - Gusmanely Z.; Sherli Yurinanda; Sarmada (Universitas Insan Budi Utomo, 2024)
Advanced calculus is a mandatory subject in the Mathematics Study Program, Faculty of Science and Technology, Jambi University. Advanced Calculus studies functions of multiple variables, ordinary derivatives, partial derivatives, double integrals, fold integrals, applications of double integrals, triple integrals and applications of triple integrals. CPL from the advanced calculus course includes students being able to develop mathematical thinking starting from procedural/computational understanding to a broad understanding including exploration, logical reasoning, generalization, abstraction and formal proof. One learning model that facilitates students to fulfill the CPL for advanced Calculus courses is the project-based learning model (Project-based Learning). It is hoped that the Project-Based Learning model can be a learning alternative to help students think creatively in learning Advanced Calculus. It is hoped that the creative thinking abilities of Mathematics Study Program students will increase and support the fulfillment of CPL courses which will result in the formation of creative and systematic mathematics students who are skilled in solving problems and have the capabilities and competencies needed by the world of work (industry, services and government). The results of the analysis showed that the creative thinking abilities of students in class R001 were classified as creative and 1 group was very creative, while in R002 all groups were classified as very creative. The conclusions of this research show a tendency for students' creative thinking abilities to be in the creative category.